Kajian Motor Tak Serempak Tiga Phasa sebagai Generator Satu Phasa dalam Penerapan Teknologi Efisiensi Energi - Pelpinus Sinay (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Asynchronous motors, commonly known as induction motors, are widely utilized due to their robustness, reliability, and efficiency in both industrial and household applications. These motors typically operate by converting electrical energy into mechanical energy through the interaction between a rotating magnetic field and the rotor. Under normal operating conditions, the rotor speed is always slightly less than the speed of the magnetic field, which is known as